Predictive biomarkers in the treatment of HER2-positive breast cancer: an ongoing challenge. (June 2016) - Triulzi, Tiziana; Bianchi, Giulia Valeria; Tagliabue, Elda
The transmembrane tyrosine kinase receptor HER2 is overexpressed in 20% of invasive breast cancers and is associated with more aggressive disease. Until the advent of targeted agents, HER2 was associated with worse outcome. Trastuzumab, a recombinant humanized anti-HER2 monoclonal antibody, combined with chemotherapy improves disease-free and overall survival in both primary and metastatic tumors and represents a foundation of care for patients with HER2-positive breast cancers. However, a sizeable number of patients do not respond to this reagent, indicating the need for a biomarker able to recognize resistant tumors. Here, we review various studies on mechanisms of action and resistance to trastuzumab that have proven relevant in understanding how tumor care can be tailored to all HER2-positive patients.